Characterization of luminescent mini-tufts in quantitative flow visualization experiments: Surface flow analysis and modelization - Chen, Lin; Suzuki, Tomohiro; Nonomura, Taku; Asai, Keisuke (Experimental thermal and fluid science, 2019)
•Experimental platform established for luminescent mini-tufts method for surface flow analysis.•Quantitative analysis method established for luminescent mini-tufts.•Surface flow topology and boundary layer parameters successfully extracted.•Physical and numerical model established for mini-tufts method. As a widely used surface flow visualization method, luminescent mini-tuft has become one challenging topic with its practical advantages in quantitative flow measurement. The luminescent mini-tufts method is preferred with its reduced size and increased luminescence, which is suitable for surface visualization measurement. To provide a standard method/procedure in quantitative analysis for luminescent mini-tuft measurement, the current study established an experimental characterization platform of luminescent mini-tufts method and conducted flat-pate model for flow analysis. The experimental system is consisted of wind tunnel and model section, high-speed image data recording system, digital image processing as well as the control system. The digital imaging processing method for result analysis is also explained, which includes the dark current image extraction, averaging, mini-tufts recognition, and tuft inclination angle/tuft angle estimation process. In this study, the steady flow characterization and quantitative flow analysis is conducted on a flat plate model (Re = 1.6 × 105–6.6 × 105), which is combined with hot-wire anemometry to investigate the basic surface flow topology and boundary layer behaviors. The method is shown capable of capturing both the steady and transient behaviors of a surface flow. Luminescent mini-tufts physical model is also established and found good agreement with the experimental results in this study, which in turn support the mini-tufts characterization and selection in practical applications.